Monitoring, Evaluation and Learning in NGO Advocacy - Findings from Co mparative Policy Advocacy MEL Review Project - Coe, Jim; Majot, Juliette (ODI, 2013)
For organizations committed to social change, advocacy often figures a s a crucial strategic element. How to assess effectiveness in advocacy is, therefore, important. The usefulness of Monitoring, Evaluation an d Learning (MEL) in advocacy are subject to much current debate. Advoc acy staff, MEL professionals, senior managers, the funding community, and stakeholders of all kinds are searching for ways to improve practi ces – and thus their odds of success – in complex and contested advoca cy environments. This study considers what a selection of leading advo cacy organizations are doing in practice. We set out to identify exist ing practice and emergent trends in advocacy-related MEL practice, to explore current challenges and innovations. The study presents percept ions of how MEL contributes to advocacy effectiveness, and reviews the resources and structures dedicated to MEL.